Different Approaches to Overcome Uncertainties of Production Systems - Azizi, Amir; Sorooshian, Shahryar (2014)
This study presented a comprehensive review on the understanding of uncertainty and the current approaches that have been proposed to handle the uncertainties in the production systems. This paper classified proposed approaches into 11 groups. The paper studied 114 scholarly papers through various international journals. The paper added the latest findings to the body of knowledge to the current reservoir of understanding of the production uncertainties. Thus, the paper prepared the needs of researchers and practitioners for easy references in this area. This review also provided an excellent source to continue further studies on how to deal with the uncertainties of production system.